Alih Fungsi Pengemis: Dari Pengangguran Menjadi Profesi. Bagaimana Islam Memandang Hal Tersebut? - Denisa Putri Rahmawan; Hisny Fajrussalam; Ghefira Nur Fatimah; Jihan Nurul Afifah; Siti Afifatul Arifah (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
This research uses qualitative methods with descriptive analysis techniques using library research or library research. The purpose of this study is to find out, examine and reveal problems regarding the conversion of beggars into a profession. Poverty in Indonesia has increased significantly which has been exacerbated by the COVID-19 pandemic. This has an impact on reducing or terminating human resource jobs and making them unemployed. Limited skills and less than optimal business makes their economy weaken and they finally try other ways to make ends meet by begging. The feeling of being happy to get money without working hard gives rise to new habits and makes them feel at home to continue it even to the point of cheating. People's awareness and trust has decreased, creating doubts about whether or not to help beggars. In Islam itself, begging is the wrong way to meet the demands of life. Islam teaches to always try hard and the need for an attitude of mutual help both in actions or actions to reduce the existence of beggars.